Ancestral Lands in Search of a Title: Revisiting Ethnic Relations and Political Alliances in the Cordilera - Soluta, Andrea G. (Silliman Journal, 2023)
This article reexamines how the Philippine government’s "developmental ideology" and economic opportunism has systematically dispossessed various indigenous peoples in the Cordillera, Northern Philippines of their lands. This paper also traces how these ancestral land issues and the subsequent push for regional autonomy — so the IPs can defend their rights to their ancestral domain through self-determination — has created a new ethnicity, called the "Cordilleran identity," as well as the modern phenomenon of indigenous peoples’ becoming interest or intensely politicized groups.